The Tracts of Imam Al-San`ani Through his Writings on the Term Ali Al-Hafiz Ibn Hajar in Al-Hadith Al-Hasan- Collection and Critical Study- (Islamic Sciences Journal, 2023)
In this research, we dealt with the tracts of Imam al-San`ani through his books on the term Ali al-Hafiz Ibn Hajar on al-Hadeeth al-Hasan.The first topic was to define the concept of tracking linguistically and idiomatically, and to define the hafiz Ibn Hajar and Imam al-San`ani, and it consisted of three demands. The second topic came to talk about the definition of good hadith. The third topic was concerned with the general and specific between the correct and good hadith . The fourth topic was about the hadith of katheer bin Abdullah in Takbirat the Eid between the correct and good, and the fifth study on the indications of good hadith and the response to Abu Al-Fath Al-Yamari, then the conclusion, and then the sources.
Keywords: Traces, good hadith, general and specific, takbeers of Eid, response .